Extent of Double Strandedness in Avian Myeloblastosis Virus RNA - Cavalieri, Liebe F. (1974)
The extent of double strandedness of avian myeloblastosis virus 70S RNA has been determined from fluorescence measurements of the intercalation of ethidium bromide. We have shown that 50% of the nucleotides of 70S RNA in solution are in a stable helical configuration. This value does not include small helical regions that are too unstable to permit intercalation of the dye. The avian myeloblastosis virus RNA as it exists within the virion has the same degree of helicity as the free 70S RNA. Heating the free 70S RNA to 55 or 70 C, followed by cooling, does not measurably change the degree of helicity; the subunits therefore have as much helicity as the parent molecule.